Do patients with syncope have a hyper-reactive autonomic nervous system?. (24th May 2021) - Perez-Denia, L; Claffey, P; O"reilly, A; Delgado-Ortet, M; Rice, C; Kenny, RA; Finucane, C
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Irish Research Council (IRC): Government of Ireland Postgraduate Scholarship Programme 2018, Dublin, Ireland Fundació Universitària Agustí Pedro i Pons, Universitat de Barcelona, Barcelona, Spain. Background: The origin of syncope, a transient loss of consciousness due to cerebral hypoperfusion, remains unclear. Recent studies suggest that a hypersensitive autonomic nervous system might be involved in the pathophysiology of vasovagal syncope (VVS). Purpose: Here we test the hypothesis that patients with VVS have a hyper-reactive autonomic nervous system by investigating the peripheral haemodynamic responses during a standing (AS) test in a group of young VVS patients vs a control group. Methods: A prospective sample of consecutive patients from a National Falls and Syncope Unit was recruited, and a convenience sample of young healthy community dwelling adults was recruited from a local university (16-30 years). Participants performed a 3 minute AS with continuous measurement of beat-to-beat blood pressure (BP), heart rate (HR), and cerebral oxygenation measured with near infrared spectroscopy. Baseline, steady-state and other time domain features were obtained for systolic BP (SBP) (i.e. nadir, overshoot, overshoot-to-nadir, overshoot-to-nadir recovery rate) and for HR (i.e. peak, trough, peak-to-trough, peak-to-trough recovery rate). Multiple linear regression was used to compare these features between patients and controls while correcting for covariates (p < 0.05 significant). Results: Forty patients and 17 controls were included, the former group being younger ((20(5.5) vs 23(1) years, p = 0.003). During steady-state standing SBP was higher as compared to controls (β: 6.853, CI: (0.713 12.993), p = 0.029). Patient data trended toward lower steady-state HR (β: -5.262, CI:(-11.201 0.677), p = 0.081), together with a larger peak-to-trough difference (β: 7.212, CI:(1.329 -15.754), p = 0.096). Conclusion: These results tend to support the hypothesis and previous literature suggesting the presence of autonomic hyper-reactivity in patients with syncope, presenting as an exaggerated peripheral circulatory response to standing. Understanding the pathophysiology of VVS can help us improve its assessment and develop better treatment pathways for these patients.